Exploiting tagline slogans as authentic materials in English for Occupational Purposes (EOP) classroom / Nor Hairunnisa Mohammad Nor ... [et al.] - Mohammad Nor, Nor Hairunnisa; Che Hassan, Nor Syamimi Iliani; Wan Mahzan, Mohd Syazwan (Universiti Teknologi MARA, Kedah, 2021)
Tagline slogans are aggressively used in the marketing field to promote specific products or services to consumers. However, they are least used as authentic materials in the teaching and learning of English as a Second Language (ESL) class. The too-brief structure embodying tagline slogans makes them difficult to be exploited to be used as materials for teaching and learning processes. Studies on the use of tagline slogans in ESL speaking lessons are still scarce, making it inconclusive to fully comprehend why they are underutilized as opposed to the other authentic materials. Therefore, this study aims to investigate the reasons for such ill preference towards the employment of tagline slogans as authentic materials in speaking lessons from the view of English for occupational purposes (EOP) students. The qualitative data of this study was obtained from seven participants who had utilized tagline slogans in their class presentations. The findings show that tagline slogans are less preferable due to inappropriate words or sentence structures used, presenters' inefficient explanation resulting in the audience' misunderstanding and suitability issues with context. Even though there lie limitations in using tagline slogans as authentic materials, with the right selection, they could act as a platform to improve learners' shared world knowledge in particular and their productive skills of the target language in the long run. This study has unearthed the case against the use of tagline slogans in speaking lessons from the lenses of EOP learners and at the same time has provided lessons learned on how tagline slogans could positively nurture learners' speaking skills.